GENDER DIFFERENTS AND VISUAL-SPATIAL INTELLIGENCE IN SOLVING GEOMETRIC IN 9TH GRADE - Ria Wahyu Wijayanti; Imam Sujadi; Sri Subanti (Proceedings Education and Language International Conference, 2017)
Visual-spatial intelligence is one of the multiple intelligences that is important to solve mathematics problem, especially in geometry. The aim of this research is to know about visual-spatial characteristic, such as students’ imagination, pattern seeking, problem solving, and conceptualization in solving the geometric problem. The type of this research was a qualitative research on case study. Subject’s selection procedure was by using snowball sampling. Data collection technique was task-based interviews. The validity was determined by time triangulation. The data analysis technique in this research was reduction, data display, and conclusion. The data was analyzed based on visual-spatial indicator. The results of this research showed that female students have better pattern seeking, problem solving, and conceptualization. Meanwhile male students have better in imagination. Keywords: gender, geometric, intelligence, visual-spatial